Nephrology eConsults for Primary Care Providers: Original Investigation. Issue 1 (22nd January 2018) - Keely, Erin; Li, Jennifer; Magner, Peter; Afkham, Amir; Liddy, Clare
Background: The Champlain BASE™ (Building Access to Specialists through eConsultation) eConsult service allows primary care providers (PCPs) to submit patient-specific clinical questions to specialists via a secure web service. Objective: Our objective was to describe the types of nephrology questions asked through an eConsult service based in eastern Ontario and assess the service's impact on the need for face-to-face consultations. Design: Cross-sectional study using descriptive statistics was conducted using nephrology cases submitted between May 2011 and January 2015. Specialist response times and referral avoidance were collected. Validated taxonomies were used to categorize cases based on question type and content. Setting: Patient cases were collected from PCPs in Ottawa, Ontario, and its surrounding communities and submitted to nephrologists at the Ottawa Hospital. Patients: During the study period, 155 eConsults were submitted to nephrology. Measurement: Utilization and survey data were collected for all eConsults. Questions were categorized by subject matter and question type. Results: A traditional consult visit was avoided in 45% of cases based on the specialist's advice; 21% cases required referral. Thirty-two percent of eConsults took specialists less than 10 minutes to complete, 55% took 10 to 15 minutes, 11% took 15 to 20 minutes, and only 2% took more than 20 minutes. Twenty-five percent of cases were related to proteinuria, 18% to chronic kidney disease (CKD), 17% to imaging, and 12% to drug use in CKD. Common question types included general management (37%), interpretation of laboratory test (17%), interpretation of an image report (13%), and need for nephrology referral (11%). Limitations: Some consults contained multiple categories and question types. Our analyses required a single classification, which may underestimate the number of questions in each category. Our study had a small sample size using cases completed in a single health jurisdiction, limiting generalizability. Conclusions: The Champlain BASE™ eConsult service provided guidance to PCPs and reduced the number of face-to-face nephrology consultations.